Frequent users of US emergency departments: characteristics and opportunities for intervention. Issue 7 (28th January 2014) - Vinton, Deborah T; Capp, Roberta; Rooks, Sean P; Abbott, Jean T; Ginde, Adit A
Abstract : Objective: To compare the characteristics of US adults by frequency of emergency department (ED) utilisation, specifically the prevalence of chronic diseases and outpatient primary care and mental health utilisation. Methods: We analysed 157 818 adult participants of the 2004–2009 US National Health Interview Survey, an annual nationally representative sample. We defined ED utilisation during the past 12 months as non-users (0 ED visits), infrequent users (1–3 visits), frequent users (4–9 visits) and super-frequent users (≥10 visits). We compared demographic data, socioeconomic status, chronic diseases and access to care between these ED utilisation groups using multivariable logistic regression. Results: Overall, super-frequent use was reported by 0.4% of US adults, frequent use by 2% and infrequent ED use by 19%. Patients reporting ≥4 ED visits were more likely to have Medicaid insurance (OR 1.57; 95% CI 1.34 to 1.85 vs private); fair or poor self-reported health (OR 2.98; 95% CI 2.57 to 3.46 vs excellent–very good); and chronic diseases such as coronary artery disease (OR 1.61; 95% CI 1.40 to 1.86), stroke (OR 1.58; 95% CI 1.36 to 1.83) or asthma (OR 1.64; 95% CI 1.46 to 1.85). While patients reporting the ED as their usual source of sick care were more likely to have ≥4 ED visits (OR 7.09; 95% CI 5.61 to 8.95 vs outpatient clinic as source), ≥10 outpatient visits in the past 12 months was also associated with frequent ED use (OR 11.4; 95% CI 9.09 to 14.2 vs no outpatient visits). Conclusions: Frequent ED users had a large burden of chronic diseases that also required high outpatient resources. Interventions designed to divert frequent ED users should focus on chronic disease management and access to outpatient services, particularly for Medicaid beneficiaries and other high risk subpopulations.